Implikasi Yuridis Adopsi Anak Terhadap Hak Waris Dan Perikatan Dalam Hukum Islam Dan Hukum Positif: Implikasi Yuridis Adopsi Anak Terhadap Hak Waris Dan Perikatan Dalam Hukum Islam Dan Hukum Positif - Dindin Syarief Nurwahyudin; Nakhma’ussolikhah (Islamic Criminal Law Study Program, Bunga Bangsa Cirebon Islamic University, 2026)
This study aims to analyze the legal implications of child adoption on inheritance rights and contractual relationships from the perspective of Islamic law and Indonesian positive law. The research employs a normative juridical approach with a descriptive-comparative analysis through the examination of statutory regulations, the Compilation of Islamic Law (KHI), as well as relevant literature and court decisions. The results indicate that under Islamic law, adoption (tabannī) does not create a legal lineage or inheritance rights between the adopted child and the adoptive parents. The adopted child is only entitled to a share of the estate through a hibah (grant) or wasiat wajibah (obligatory will) as stipulated in Article 209 of the KHI. Conversely, under Indonesian positive law, adoption is recognized as a legitimate legal act based on a court decision that establishes full civil relations, including reciprocal rights and obligations between the adopted child and the adoptive parents. Although there are fundamental differences in their legal foundations and consequences, both systems share the same objective—ensuring the protection and welfare of the child. This study emphasizes the importance of harmonizing Islamic law and positive law to ensure that adoption practices in Indonesia provide legal certainty while upholding justice and moral-religious values. Keywords: child adoption, inheritance rights, contractual relationship, Islamic law, Indonesian positive